Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 12 seriously the problem of the downward trend in population ; a Royal Commission is appointed ; speeches are made about the sacred duty of parenthood. And meanwhile this terrible wastage of life is allowed to continue. A comparison of the infant mortality rates of prosperous middle-class districts with those of industrial areas fortifies the conclusion that the children of the working class are murdered in huge numbers by their environment. The following figures are for 1934 :— Hastings 35 Canterbury 38 Hertfordshire 38 Barrow-in-Furness 98 Salford 92 Gateshead 87 (2) Maternal Mortality. This is also partly dependent on environment, although the effect of poverty is modified to a variable extent according to the adequacy of local services. The following table gives examples of material mortality rates in 1934 :— The Soke of Peterborough 1.31 Bath 1.32 East Ham 1.48 Burnley 14.57 Barrow-in-Furness 11.88 Merionethshire 11.75 Expectant mothers of the well-to-do classes eat extra nourishing food ; those of the poor cannot afford a diet adequate for health in normal times, let alone purchase the expensive foods which doctors recommend during pregnancy. The effect of malnutrition on maternal mortality was demonstrated by an experiment carried out in the Rhondda Valley in 1935-37. One group of expectant mothers was provided with additional food and another only with improved medical services. It was found that in the first maternal mortality was 1.63 per 1,000 births, while in the second it was 6.15. Again, while the well-to-do expectant mother has taken a carefully regulated amount of exercise and avoided overstrain, the working class woman has borne the whole burden of domestic drudgery, right up to the time of her confinement, in an osbolete [obsolete] house unprovided with modern conveniences even of the most elementary kind. (3) The Death Rate. In general the death rate is highest among the poorest section of the community. Dr. McGonigle in 1931-34 surveyed the working-class of Stockton-on-Tees, comparing the death rates of the unemployed section of it with that of those in employment. His results are shown below:—* Unemployed Employed Average income 29/2½ 51/6 Average size of family 4.26 3.83 Crude death rate 31 9 Standardised death rate 26 11½ * Adapted from Condition of Britain, p.95. 15X/2/98/13